DISTRIBUTED IOT BASED SMART WASTE MANAGEMENT SYSTEM - Ikhlayel, Aseel; Manasrah, Sally (جامعة بوليتكنك فلسطين - هندسة حاسوب, 2021)
In the present days, the garbage bins or trash cans which are placed at public places in the cities are getting overflow due to increase in the waste every day. It creates bad health conditions for people by spreading some deadly diseases . To avoid such situations , planning to design smart bins means that the particular authorities can receive messages about the bins’ status . So, our system serves particularly municipal employees , saves their time and reduces cost also . It provides smart waste management solutions for cities and businesses to cost effectively manage the waste , improve the environment and wellbeing of people . The system aims to improve the waste collection process and its operation efficiency, manage, understand and separate the waste type (either liquid or solid), thus knowing the possibility of recycling the waste .This is done through involving unique ultrasonic smart sensors that monitor waste in real-time using IoT. Thus provides cities and businesses with data-driven decision making, and optimization of waste collection routes.As trash increases , the distance between the ultrasonic and the trash decreases, this data will be sent to our micro-controller. Microcontroller then processes the data and sends messages to the android app which alerts the responsible staff. After that, the collected data is analyzed ,then the instructions and the schedules are updated accordingly. Keywords : IOT, Internet of things, Waste management, RTOS, Raspberry PI, 3G SIM Module.
no of pages 92 , هندسة حاسوب 4/2021
Keywords: SMART WASTE; IOT